Management of Investment Activity of IT Enterprises - Panchenko Volodymyr A.; Panchenko Oksana P. (Bìznes Inform, 2023)
The article characterizes the priority importance of IT enterprises for the country’s economy and strengthening of this importance as it ensures adaptation and response to globalization changes and hybrid aggression. The importance of increasing the number of IT enterprises and the corresponding intensification of the State-based investment support is emphasized. According to this, the purpose of the article is highlighted, which provides for the scientific substantiation of the conceptual provisions of the investment management system of IT enterprises and the development of its mechanism, with the separation of individual groups of its elements in accordance with industry affiliation. An analysis of the latest publications of scientists is carried out and some approaches to the formation of a system for managing the investment activities of IT enterprises are allocated, in particular, administrative-protectionist, economic-liberal, based on security policy, etc. The requirements for managing the investment activities of IT enterprises are presented. A mechanism for managing the investment activities of IT enterprises has been developed, the elements of which are: subjects (internal, external); objects (technologies, innovations, human capital, products, business image, research and development, integration and cooperation relations); principles (payback, efficiency, dynamism, minimal risk, development, adaptability); functions (analysis, planning, organization, control, regulation, motivation); methods (organizational, technological, information, economic, legal, integration); tasks (attraction, accumulation, efficient distribution, expansion, social responsibility of investments); instruments (institualization. integration, partnership, differentiation, modernizing, incentives). It is concluded that the effectiveness of investment activity in the IT sphere depends on many factors and it is quite difficult to predict their impact, which requires enterprises to improve the management system.